PERANCANGAN STRATEGI PENGELOLAAN PELANGGAN BERDASARKAN TAHAP PERTUMBUHAN ORGANISASI PT MAPID - Winda Damaranti, Nadia
PT MAPID is a SaaS startup that plays a role in geospatial data management. Based on historical data, the number of PT MAPID subscribers increased during the period when a competition event was held and required participants to subscribe to products indirectly. Meanwhile the number of customers in other normal periods is relatively low with numbers below 15 customers. This number is far below the average number of customers for public SaaS companies, which is 36,000 customers. To solve this problem, PT MAPID needs a customer relationship management that aims to acquire potential customers and retain existing customers. In addition, information regarding the organization growth stages can help determine a strategy that suits the current characteristics of the company. Therefore, this study aims to design a customer relationship management for PT MAPID based on organization growth stages. This research was carried out qualitatively by involving thematic analysis techniques. A number of stages were carried out, including identification of organizational growth stages using ASTRO ITB, identification of customer acquisition/retention strategy orientation, customer relationship management audit, evaluation, and design. The audit process utilized a CRM audit questionnaire which includes an assessment of the process variables of strategy development, value creation, multi-channel integration, information management, and performance assessment. The results of this study indicate that currently PT MAPID is in the expansion stage and focuses on customer acquisition strategies. The evaluation’s results also show that currently PT MAPID still needs to maintain focus on its acquisition strategies and prioritize improvement to the value creation process variable. Therefore, a guideline for the pricing page on the PT MAPID website was made to enhance the value of supplementary services, particularly for potential customers.